A polymorphism at codon 31 of gene p21 is not associated with primary open angle glaucoma in Caucasians - Ressiniotis, Thomas (BioMed Central, 2005)
BACKGROUND: Primary open angle glaucoma (POAG) is considered to be a neurodegenerative optic neuropathy, in which cell death occurs by apoptosis. p21, is an important protective component of the apoptotic pathway, regulating cellular arrest in the presence of DNA damage. An unstable or altered p21 protein could modify the cellular response to genomic injury and abolish the effect of p21. A previous study on a Chinese cohort suggested that the p21 codon 31 polymorphism may alter the state of apoptosis in glaucomatous optic neuropathy, failing to protect the ganglion cells. The aim of this study was to test the hypothesis that a p21 codon 31 polymorphism is associated with POAG on a Caucasian cohort. METHODS: 140 POAG patients and a control group of 73 healthy individuals were included in the study. All the subjects were of Caucasian origin. Genomic DNA was amplified by polymerase chain reaction, followed by enzymatic restriction fragment length polymorphism technique (PCR-RFLP). Patients and controls were genotyped for a single nucleotide polymorphism (C/A transversion) in the third base of codon 31 of p21, which leads to a serine (Ser)/arginine (Arg) substitution. RESULTS: The distribution of the genotypes in the POAG patients showed 128 (91.4%) Ser homozygotes, 10 (7.1%) Ser/Arg heterozygotes and 2 (1.5%) Arg homozygotes. In the control cohort, there were 61 (83.6%) Ser homozygotes and 12 (16.4%) Ser/Arg heterozygotes. No Arg homozygotes were present amongst the control group. Both the allelic and genotypic frequencies of the Ser or Arg residues at codon 31 were not significantly different between POAG patients and controls (Fisher's exact test, P = 0.20 for alleles and P = 0.0561 for genotypes). CONCLUSION: This study suggests that the p21 codon 31 polymorphism does not contribute to the risk of POAG in the Caucasian population.